Pengembangan Bahan Ajar Berbasis Potensi Daerah Sebagai Pendukung Pembelajaran Tematik - Dwi Yani; Nibras Alhama Najwa; Almanik Dyan Permatasari; Dinenggi Wulanoventi; Herawati Susilo; Aynin Mashfufah (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the development process, the feasibility of teaching materials, and students' responses to printed teaching materials. This study uses the ADDIE development model. Limited trials in this study were carried out on 23 grade VI students at SDN Trawas 1 Mojokerto. The data collection technique was carried out using a review test, a validation test on several experts and a student response questionnaire. The results of this study show the feasibility of the content of the material by 87% with very feasible criteria, presentation feasibility of 83% with very feasible criteria, language feasibility of 88% with very feasible criteria, and graphic feasibility of 80% with feasible criteria, as well as the results of the response questionnaire students by 93% with very good criteria